Tratamiento quirúrgico y de rehabilitación de las Distrofias Musculares. Recomendaciones basadas en la evidencia para la Guía de Práctica Clínica en Colombia (2016)
ABSTRACT: Surgical and rehabilitation treatment for patients with Muscular Dystrophies. Evidence-based recommendations for clinical practice guidelines in Colombia Muscular dystrophies (MD) are genetic diseases that cause progressive weakness and degeneration of muscles. The Guide to clinical practice for early detection, comprehensive care, monitoring and rehabilitation of patients diagnosed with muscular dystrophy developed recommendations for the comprehensive care of patients diagnosed with the most common MD. The Methodological guide for the development of clinical practice guidelines with economic assessment in the general social security system in health of Colombia was used, which mainly includes the use of the GRADE methodology. This article includes recommendations related to the surgical and rehabilitation treatment of people with MD. In general, we recommend spinal fixation surgery, elongation of the Achilles tendon, scapular fixation and tendon elongation; also the use of positive pressure devices, respiratory therapy, exercises of submaximal strengthening and aerobics, avoid prolonged immobility, use of knee ankle foot orthotic, manual and motorized wheel chairs, previously examining the feasibility of prescribing them and the patient, psychological intervention, family therapy and the use of functional scales. Spinal orthoses, high resistance exercises and leisure and recreational therapies are not recommended.